2009
DOI: 10.1002/cncr.24302
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate antigen 19‐9 change during chemotherapy for advanced pancreatic adenocarcinoma

Abstract: Low‐density polyethylene (LDPE) composites modified with a resin based on ethylene/methacrylic acid copolymer (surlyn) and/or citric acid were electron beam‐irradiated and investigated by electron spin resonance (ESR) at room temperature. ESR studies were carried out directly after irradiation and after various time intervals up to 72 h postirradiation. The irradiated samples showed the ESR spectrum of seven lines that was assigned to the formation of allyl radical. The nature and yield of the allyl radical of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 38 publications
7
66
0
2
Order By: Relevance
“…Patients with a higher percent decline in CA 19-9 serum levels following treatment had improved overall survival (Group III-16.7 months compared to Group II-10 months, p<0.002, and Group II-10 months vs. 6.5 months for Group -I, p<0.002). Overall, the median survival was 15.5 months among patients with normal CA 19-9 levels, 11.9 months among 108 patients with CA 19-9 serum levels between 38 U/ml and 1,167 U/ml and 8 months among 105 patients who had CA 19-9 serum levels >1,167 U/ml [60].…”
Section: Ca 19-9 Serum Levels As a Biomarker For Chemotherapy Responsmentioning
confidence: 93%
See 2 more Smart Citations
“…Patients with a higher percent decline in CA 19-9 serum levels following treatment had improved overall survival (Group III-16.7 months compared to Group II-10 months, p<0.002, and Group II-10 months vs. 6.5 months for Group -I, p<0.002). Overall, the median survival was 15.5 months among patients with normal CA 19-9 levels, 11.9 months among 108 patients with CA 19-9 serum levels between 38 U/ml and 1,167 U/ml and 8 months among 105 patients who had CA 19-9 serum levels >1,167 U/ml [60].…”
Section: Ca 19-9 Serum Levels As a Biomarker For Chemotherapy Responsmentioning
confidence: 93%
“…Whether serum CA 19-9 levels can be used as a surrogate marker of response to chemotherapy has been studied in a variety of clinical settings [41,44,[53][54][55][56][57][58][59][60][61][62][63][64]. Willett et al measured CA 19-9 serum levels in 42 resectable pancreatic cancer patients receiving neoadjuvant treatment with 5-flourouracil and external beam radiation prior to planned pancreaticoduodenectomy.…”
Section: Ca 19-9 Serum Levels As a Biomarker For Chemotherapy Responsmentioning
confidence: 99%
See 1 more Smart Citation
“…A major biochemical response (ie, a reduction 90% in CA 19-9 concentration at nadir compared with the baseline value) appeared to correlate with to better OS in biliary tract cancer, as we observed previously in pancreatic cancer. 42 Clinical trials are difficult to perform because of the relative rarity and heterogeneity of these tumors and because of the patient population. In the last 22 years, there were >100 clinical trials, including only 2 phase 2 randomized trials 10,33 and 1 phase 3 trial, 36 with a mean of 25 patients per trial and with limited sample sizes in various disease subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in serum tumour markers have been explored for the latter purpose. Small patient series in PC have indicated that changes in CA19-9 during treatment provide clinically relevant information (5)(6)(7)(8)(9)(10), but the value of these changes is far from established (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%